INOVASI LAPOR HENDI (LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT) DI KOTA SEMARANG - Maulida Adypurnawati; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Innovation of public service must be performed by government, so that the public services provided can be more effective and efficient. Online People's Aspiration and Complaint Service or LAPOR Hendi is an innovation of public service at the initiative of the Mayor of Semarang. LAPOR Hendi is a means of aspiration and complaints in order to increase public participation in controlling the development and implementation of public services for information and evaluation of Semarang City Government performance. This study uses a qualitative method with a descriptive approach. This research uses atributes of innovation theory from Rogers, driving factor of innovation theory from Rogers, and obstacle theory of innovation theory from Suwarno. The results of this study indicate that LAPOR Hendi innovations have 1) relative advantages, 2) compability, 3) triability and 4) observability, but still have complexity. In its implementation, LAPOR Hendi innovation has a motivating factors, that is the desire to change oneself’s, freedom to expression, broad-minded and creative counselors, the availability of facilities and infrastructure, and a harmonious environment. However, the innovation of LAPOR Hendi has inhibiting factors in its implementation, i.e. dependence on certain figures, lack of appreciation, inability to face risks, and administrative pressure. The writer suggests to maintain collaborative and cooperative relationships with interested parties, to improve the ability of employees in the field of information and technology, giving awards to employees, and giving socialization of information regarding the requirements for filing complaints.